Strategi Pemasaran Produk Asuransi Syariah Di PT. Prudential Life Assurance Cabang Kota Medan - Febby Ayu Syahputri Gurning; Nuri Aslami (Yayasan Literasi Sains Indonesia, 2022)
Human life in modern times has various kinds of risks and dangers. Man himself does not know what will happen tomorrow and where he will die world. Insurance is a financial tool for managing home life, both in terms of facing an underlying risk, such as the chance of mortality, and in terms of protecting one's personal belongings. In the marketing process, a strategy is needed essential, the company's main target in a broad market reach. So that a strategy is required before entering the market, all of the plans have been consolidated, comprehensive, And included to make sure that the company's last purpose may be found out via the implementation of the suitable strategy. Study The reason for this observation is to choose and evaluate (segmentation, targeting, and positioning) at PT. Prudential Life Assurance Medan City Branch, in addition to to decide whether or not the advertising plan is carried out according with sharia advertising characteristics. This study employs a qualitative technique while doing descriptive research. The findings revealed that the market segmentation (segmenting) conducted by PT. Prudential Life Assurance Medan City Branch based on per market grouping region. To make it easier for Prudential to meet and greet its customers return. Targeting, in determining the target market covered by PT. Prudential Life Assurance Medan City Branch there is no certain limit, the company serves all market segment.